Patterns and Determinants of International Trade Costs in the Food Industry - Alessandro Olper; Valentina Raimondi (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2007)
This paper documents patterns in international trade costs in processed foods for a large cross-section of developing and developed countries, during the 1976-2000 period. A trade costs index is inferred from a micro-founded gravity equation that incorporates bilateral `iceberg?trade costs. For 2000, the weighted average tariff equivalent of trade costs ranges from 73% for the North to 134% for the South countries. The time patterns show an average reduction of about -13% in the observed period, that rises to -26% for the Emerging countries. However, the same does not apply for South countries. On ranking the trade costs detfirminants we find that, on average, geographical and historical factors seem to dominate those of infrastructure and institutions. However, trade policy emerges as an important detfirminant of the North-Emerging trade costs. Finally we find strong evidence that demand-side considerations also matter to explain trade costs.
Keywords: F1; F13; F14; 330; Trade costs; Gravity; Processed Foods; Geography; Infrastructure; Trade Policy; Inequality; Lebensmittelhandel; Außenhandel; Transaktionskosten; Entwicklungsländer; Schwellenländer; Industriestaaten